Modeling the potential public health and economic impact of different COVID-19 vaccination strategies with an adapted vaccine in the Kingdom of Saudi Arabia - Nadine Al Akoury; Julia Spinardi; Hammam Haridy; Mostafa Moussa; Mohammed Attia Elshabrawi; Carlos Fernando Mendoza; Jingyan Yang; Josie Dodd; Moe H. Kyaw; Benjamin Yarnoff (Expert Review of Vaccines)
Background The dynamic evolution of the virus causing COVID-19 necessitates the development of adapted vaccines to protect against emerging variants.Research design and methods A combined Markov-decision tree model estimated the outcomes of alternative vaccination strategies. The Saudi Arabian population was stratified into standard-risk and high-risk subpopulations, defined as either the population comprising individuals aged ≥ 65 years and individuals with at least one comorbidity. The model estimated the health and economic outcomes of vaccination based on age-specific inputs taken from published sources and national surveillance data.Results The vaccination strategy targeting the elderly and high-risk subpopulation (was estimated to prevent 156,694 cases 12,800 hospitalizations, and 2,919 deaths and result in cost savings of SAR 1,239 million in direct costs and SAR 4,145 million in indirect costs. These gains increased with the vaccination strategies additionally targeting other subpopulations. Compared to the base case (aged ≥65 and those at high-risk), expanding vaccination coverage to 75% of the standard-risk population prevented more cases (323%), hospitalizations (154%), and deaths (60%) and increased the direct (232%) and indirect (270%) cost savings.Conclusions The adoption of broad vaccination strategies using a vaccine adapted to the dominant variant in circulation would yield substantial benefits in Saudi Arabia.